2019
DOI: 10.1177/2045894019882636
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of inferior vena cava filter in complicated pulmonary embolism

Abstract: Background: Previous observational studies suggest that inferior vena cava filter placement in pulmonary embolism patients complicated with congestive heart failure, mechanical ventilation, and shock may have a mortality benefit. We sought to analyze the survival benefits of inferior vena cava filter in pulmonary embolism patients complicated with acute myocardial infarction, acute respiratory failure, shock, or requiring treatment with thrombolytics. Methods: This retrospective observational study used hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…Patients with and without IVC filter placement with complicated PE were 1:1 propensity score matched for demographics, DVT, Elixhauser Comorbidity Index and other PE comorbidities. Their study found that IVC filter placement reduced mortality rates overall and in each subgroup, corroborating Stein et al’s findings that IVC filters may provide greater benefit in gravely ill patients [ 50 ].…”
Section: Reviewsupporting
confidence: 72%
“…Patients with and without IVC filter placement with complicated PE were 1:1 propensity score matched for demographics, DVT, Elixhauser Comorbidity Index and other PE comorbidities. Their study found that IVC filter placement reduced mortality rates overall and in each subgroup, corroborating Stein et al’s findings that IVC filters may provide greater benefit in gravely ill patients [ 50 ].…”
Section: Reviewsupporting
confidence: 72%
“…If DVT exists before surgery, anticoagulation therapy might be ineffective or contraindicated or the proximal DVT, then IVCF insertion can be considered [15]. IVCF has been proven effective in preventing DVT and PE, as well as improving prognosis [17,18]. Nevertheless, lter penetration and fracture as well as the risk of DVT after IVCF insertion has raised concern [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Rather than a procedural complication, this in-hospital mortality rate reflects the clinical severity of presentation of the patients who received the IVC filters. Unfortunately, we do not have access to patients' demographics and comorbidities, which are known to strongly affect mortality in these cases, such as age, presence of pulmonary embolism associated with acute respiratory syndrome or shock (24), advanced stage cancer (25,26) and severe trauma (27), which is a limitation of our study. Nonetheless, the stable distribution of deaths following IVC filter placement over the years, observed in all regions, indicate that even though more IVC filters are being placed recently, the profile of the patients who are receiving them remains similar in terms of severity.…”
Section: Mortality Datamentioning
confidence: 99%